Preparation method of sodium hyaluronate composite solution for injection
By using materials such as sodium hyaluronate and polylactic acid microspheres to process low crosslinking gel and filling polymer pipelines, the problem of short degradation time and poor resolubleness in the human body is solved. , achieving more uniform injection and longer use time, reducing the risk of foreign body reaction.
Patent Information
- Application Number
- CN202411044058.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-13
AI Technical Summary
The existing sodium hyaluronate solution for injection has a short degradation time in the human body, and the composite material has poor redissolvation and dispersion in the aqueous solution, resulting in uneven distribution and foreign matter reaction during injection, and there are bubble problems, which increases production costs.
Sodium hyaluronate, polylactic acid microspheres, amino acids, sodium chloride, sodium dihydrogen phosphate and disodium hydrogen phosphate were mixed with specific ratios of injection water, and after low crosslinking gel treatment and two vacuum treatments, combined with Polymer pipe filling eliminates bubbles and improves product durability.
It extends the degradation time of sodium hyaluronate, improves uniformity and comfort during injection, reduces the risk of foreign body reaction, and improves the durability and effectiveness of the product.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium hyaluronate gel, and in particular to a method for preparing a sodium hyaluronate composite solution for injection. Background Art
[0002] The aging of the human face is affected by multiple factors, including genetic defects, light, inflammation and disease. The main characteristics include soft tissue loss, collagen loss, and decreased skin hydration, which cause fine lines and wrinkles on the face. Sodium hyaluronate filling needles support the sunken parts of the face by physically filling, making the face flat and making people younger. However, there are some disadvantages of injectable sodium hyaluronate solution. First, sodium hyaluronate will be absorbed in the human body and has a short degradation time, generally not exceeding 1 year. In order to further extend the maintenance time of the filling material, the degradable polymer microsphere material is compounded with sodium hyaluronate to extend the degradation time. Secondly, the composite materials on the market have poor resolubility and dispersibility in aqueous solution, and are easy to aggregate and precipitate, which leads to easy needle blockage during intradermal injection, increased pain caused by the use of thicker needles during injection, uneven distribution of injection materials, and easy appearance of subcutaneous nodules after injection. There are also foreign body reactions, such as redness, swelling, and inflammation. At the same time, there are bubbles in the sodium hyaluronate composite solution for injection. One of the reasons is that in order to increase the clarity of the gel after filling, the sodium hyaluronate gel will use filter element filtration and other operation methods. The filtered sodium hyaluronate gel will produce more bubbles, thereby reducing the product yield and increasing production costs. Therefore, in order to avoid the above production problems, the present invention develops a method for preparing a sodium hyaluronate composite solution for injection. Summary of the invention
[0003] In view of this, the present invention develops a method for preparing a sodium hyaluronate composite solution for injection.
[0004] The technical solution of the present invention is achieved in this way:
[0005] A method for preparing a sodium hyaluronate composite solution for injection, comprising the following raw materials in parts by weight: 10-20 parts of sodium hyaluronate, 3-5 parts of polylactic acid microspheres, 0.2-2.0 parts of amino acids, 0.3-1.5 parts of sodium chloride, 0.01-0.06 parts of sodium dihydrogen phosphate, 0.01-0.25 parts of disodium hydrogen phosphate, and 80-90 parts of water for injection, comprising the following steps:
[0006] S1. The amino acid, sodium chloride, sodium dihydrogen phosphate, disodium hydrogen phosphate and water for injection were mixed and stirred at room temperature to obtain a mixed solution 1;
[0007] S2. Weigh sodium hyaluronate and polylactic acid microspheres, and soak them in water for injection for ≥ 6 hours;
[0008] S3. After the soaking in step S2 is completed, 20-30% sodium hydroxide solution is added, and after stirring for 20-30 minutes, 1,4-butanediol diglycidyl ether is added, and the mass volume ratio of sodium hyaluronate, sodium oxide solution and 1,4-butanediol diglycidyl ether is (10-20) mg: (10-12) mL: (0.05-0.15) mL to obtain a mixed solution II;
[0009] S4. Place the mixed solution II in a water bath at 20-25°C and keep the temperature constant for 10-15h to obtain a low cross-linking gel;
[0010] S5. The low cross-linked gel was homogenized and granulated, and the sieves for homogenization granulation were 5 meshes, the first mesh was 80 mesh, the second mesh was 100 mesh, the third mesh was 200 mesh, the fourth mesh was 300 mold, and the fifth mesh was 500 mesh to obtain homogenous gel particles;
[0011] S6. The homogeneous gel particles are mixed with the mixed solution 1, vacuumed twice, and stirred in the transverse and axial directions to obtain a mixed solution III;
[0012] S7. Fill the syringe with the mixed solution III.
[0013] Furthermore, the sodium hyaluronate has an intrinsic viscosity of 1.0-3.0 mL / g.
[0014] Furthermore, the mass ratio of the amino acid, sodium chloride, sodium dihydrogen phosphate, sodium hydrogen phosphate and water for injection in S1 is (0.2-2.0):(0.3-1.5):(0.01-0.06):(0.01-0.25):(55-60), and the mass ratio of the sodium hyaluronate, polylactic acid microspheres and water for injection in S2 is (10-20):(3-5):(25-30).
[0015] Furthermore, the stirring in S1 has a rotation speed of 100-200 r / min, stirring for 60-100 min, and a temperature of 15-20°C.
[0016] Furthermore, the particle size of the polylactic acid microspheres is 5-10 microns, and the polylactic acid microspheres are one or more of PLGA, PLGA-PEG, and PLLG-PEG microspheres, and the molecular weight is 10,000-30,000;
[0017] Furthermore, in S6, the vacuum is drawn twice. The first time, the stirring is performed for 20-24 hours, and the vacuum is drawn for 10-15 minutes, and the vacuum degree is: -0.05 to -0.06 MPa. The second time, the stirring is performed for 45-48 hours, and the vacuum is drawn for 30-35 minutes, and the vacuum degree is: -0.02 to -0.03 MPa.
[0018] Furthermore, in the vacuuming process described in S6, a condensation baffle is added to the top of the preparation tank, the temperature of the condensation baffle is set to 2-5°C, and the stirring paddle stirs horizontally and axially at the same time.
[0019] Furthermore, in S7, the mixed solution III is filled, and the filling is connected to the filling needle using a polymer pipeline, the outer layer of the polymer pipeline is polytetrafluoroethylene, and the inner layer is silicone rubber, and the hardness of the silicone rubber is 80-90A.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention provides a method for preparing a sodium hyaluronate composite solution for injection, wherein amino acids, sodium chloride, sodium dihydrogen phosphate, sodium hydrogen phosphate and water for injection are compounded, and polylactic acid microspheres are added to increase the durability and effectiveness of the product.
[0022] (1) The process of stirring twice and vacuuming twice, adding a condensation baffle on the top of the filling, and transporting the polymer through a pipeline for filling effectively eliminates bubbles in the composite solution. The low cross-linking technology and the addition of 1,4-butanediol diglycidyl ether after sodium hyaluronate and microspheres are soaked avoid the problem of polylactic acid microsphere stratification during product storage.
[0023] (2) Polymer pipelines are used to transport materials for filling to avoid bubbles during filling. PLGA, PLGA-PEG, and PLLG-PEG polylactic acid microspheres with a molecular weight of 10,000 to 30,000 are added to improve the effectiveness and durability of product use.
[0024] (3) The problem of stratification of polylactic acid microspheres during storage is avoided by soaking the microspheres with sodium hyaluronate and then adding sodium hydroxide solution and stirring to add 1,4-butanediol diglycidyl ether. DETAILED DESCRIPTION
[0025] In order to better understand the technical content of the present invention, specific examples are provided below to further illustrate the present invention. The experimental methods used in the examples of the present invention are all conventional methods unless otherwise specified.
[0026] Unless otherwise specified, the materials and reagents used in the examples of the present invention can be obtained from commercial sources.
[0027] Example 1
[0028] A method for preparing a sodium hyaluronate composite solution for injection, comprising the following raw materials in parts by weight: 15 parts of sodium hyaluronate, 4 parts of polylactic acid microspheres, 1 part of amino acid, 1 part of sodium chloride, 0.04 parts of sodium dihydrogen phosphate, 0.02 parts of disodium hydrogen phosphate, and 80 parts of water for injection, and the preparation steps are as follows:
[0029] (1) Amino acid, sodium chloride, sodium dihydrogen phosphate, sodium hydrogen phosphate and water for injection in a mass ratio of 1:1:0.04:0.02:55 are mixed and stirred at room temperature at a stirring speed of 200 r / min, a stirring time of 60 min and a temperature of 20° C. to obtain a mixed solution 1;
[0030] (2) Weighing sodium hyaluronate and polylactic acid microspheres in a mass ratio of 15:4:25, adding them to injection water for immersion for 8 hours, wherein the intrinsic viscosity of sodium hyaluronate is 2 mL / g, the particle size of polylactic acid microspheres is 8 μm, and the polylactic acid microspheres are PLGA and PLGA-PEG, with a molecular weight of 15,000;
[0031] (3) After the soaking in step (2) is completed, add 20% sodium hydroxide solution, stir for 25 minutes, then add 1,4-butanediol diglycidyl ether, the mass volume ratio of sodium hyaluronate, sodium hydroxide solution and 1,4-butanediol diglycidyl ether is 15:10:0.1 mg / ml to obtain a mixed solution II;
[0032] (4) placing the mixed solution II in a water bath at 25°C and keeping the temperature constant for 15 hours to obtain a gel with a low cross-linking degree;
[0033] (5) homogenizing and granulating the low cross-linked gel, wherein the sieves for homogenizing and granulating are 5-mesh sieves, wherein the first sieve is 80 mesh, the second sieve is 100 mesh, the third sieve is 200 mesh, the fourth sieve is 300 mesh, and the fifth sieve is 500 mesh, to obtain homogenous gel particles;
[0034] (6) The homogeneous gel particles were mixed with the mixed solution 1 and vacuumed twice. During the vacuuming process, a condensation baffle was added to the top of the preparation tank and the temperature of the condensation baffle was set to 3°C. The mixture was vacuumed twice. When the mixture was stirred for 20 hours for the first time, the mixture was vacuumed for 10 minutes and the vacuum degree was -0.05 MPa. When the mixture was stirred for 45 hours for the second time, the mixture was vacuumed for 30 minutes and the vacuum degree was -0.02 MPa. After vacuuming, the mixture was stirred in the transverse and axial directions at the same time to obtain a mixed solution III.
[0035] (7) Filling the mixed solution III into a syringe, the filling is carried out by connecting a polymer tube to the filling needle, the outer layer of the polymer tube is polytetrafluoroethylene, the inner layer is silicone rubber, and the hardness of the silicone rubber is 80A.
[0036] Example 2
[0037] A method for preparing a sodium hyaluronate composite solution for injection, comprising the following raw materials in parts by weight: 20 parts of sodium hyaluronate, 5 parts of polylactic acid microspheres, 2 parts of amino acids, 1.5 parts of sodium chloride, 0.05 parts of sodium dihydrogen phosphate, 0.25 parts of disodium hydrogen phosphate, and 90 parts of water for injection, and the preparation steps are as follows:
[0038] (1) Amino acid, sodium chloride, sodium dihydrogen phosphate, disodium hydrogen phosphate and water for injection in a mass ratio of 2:1.5:0.05:0.25:60 are mixed and stirred at room temperature at a stirring speed of 200 r / min, a stirring time of 100 min and a temperature of 15° C. to obtain a mixed solution 1;
[0039] (2) Weighing sodium hyaluronate and polylactic acid microspheres in a mass ratio of 20:5:30, adding them to injection water for immersion for 9 hours, wherein the intrinsic viscosity of sodium hyaluronate is 1 mL / g, the particle size of polylactic acid microspheres is 5 μm, and the polylactic acid microspheres are PLLG-PEG microspheres with a molecular weight of 20,000;
[0040] (3) After the soaking in step (2) is completed, 30% sodium hydroxide solution is added, and after stirring for 30 minutes, 0.1,4-butanediol diglycidyl ether is added. The mass volume ratio of sodium hyaluronate, sodium hydroxide solution and 1,4-butanediol diglycidyl ether is 20:10:0.1 mg / ml to obtain a mixed solution II;
[0041] (4) placing the mixed solution II in a water bath at 25°C and keeping the temperature constant for 10 hours to obtain a gel with a low cross-linking degree;
[0042] (5) homogenizing and granulating the low cross-linked gel, wherein the sieves for homogenizing and granulating are 5-mesh sieves, wherein the first sieve is 80 mesh, the second sieve is 100 mesh, the third sieve is 200 mesh, the fourth sieve is 300 mesh, and the fifth sieve is 500 mesh, to obtain homogenous gel particles;
[0043] (6) The homogeneous gel particles were mixed with the mixed solution 1 and vacuumed twice. During the vacuuming process, a condensation baffle was added to the top of the preparation tank and the temperature of the condensation baffle was set to 2°C. The mixture was vacuumed twice. When the mixture was stirred for 22 hours for the first time, the mixture was vacuumed for 12 minutes and the vacuum degree was -0.06 MPa. When the mixture was stirred for 48 hours for the second time, the mixture was vacuumed for 35 minutes and the vacuum degree was -0.03 MPa. After vacuuming, the mixture was stirred in the transverse and axial directions at the same time to obtain a mixed solution III.
[0044] (7) Filling the mixed solution III into a syringe, the filling is carried out by connecting a polymer tube to the filling needle, the outer layer of the polymer tube is polytetrafluoroethylene, the inner layer is silicone rubber, and the hardness of the silicone rubber is 80A.
[0045] Example 3
[0046] A method for preparing a sodium hyaluronate composite solution for injection, comprising the following raw materials in parts by weight: 10 parts of sodium hyaluronate, 3 parts of polylactic acid microspheres, 0.2 parts of amino acids, 0.3 parts of sodium chloride, 0.01 parts of sodium dihydrogen phosphate, 0.01 parts of disodium hydrogen phosphate, and 90 parts of water for injection, and the preparation steps are as follows:
[0047] (1) Amino acid, sodium chloride, sodium dihydrogen phosphate, sodium hydrogen phosphate and water for injection in a mass ratio of 0.2:0.3:0.01:0.01:60 are mixed and stirred at room temperature at a stirring speed of 100 r / min, a stirring time of 70 min and a temperature of 18° C. to obtain a mixed solution 1;
[0048] (2) Weighing sodium hyaluronate and polylactic acid microspheres in a mass ratio of 10:3:30, adding them to injection water for immersion for 9 hours, wherein the intrinsic viscosity of sodium hyaluronate is 2 mL / g, the particle size of polylactic acid microspheres is 10 μm, and the polylactic acid microspheres are PLGA-PEG and PLLG-PEG, with a molecular weight of 25,000;
[0049] (3) After the soaking in step (2) is completed, add 25% sodium hydroxide solution, stir for 20 minutes, then add 1,4-butanediol diglycidyl ether, the mass volume ratio of sodium hyaluronate, sodium hydroxide solution and 1,4-butanediol diglycidyl ether is 10:10:0.1 mg / ml to obtain a mixed solution II;
[0050] (4) placing the mixed solution II in a water bath at 25°C and keeping the temperature constant for 15 hours to obtain a gel with a low cross-linking degree;
[0051] (5) homogenizing and granulating the low cross-linked gel, wherein the sieves for homogenizing and granulating are 5-mesh sieves, wherein the first sieve is 80 mesh, the second sieve is 100 mesh, the third sieve is 200 mesh, the fourth sieve is 300 mesh, and the fifth sieve is 500 mesh, to obtain homogenous gel particles;
[0052] (6) The homogeneous gel particles were mixed with the mixed solution 1 and vacuumed twice. During the vacuuming process, a condensation baffle was added to the top of the preparation tank and the temperature of the condensation baffle was set to 5°C. The mixture was vacuumed twice. When the mixture was stirred for 24 hours for the first time, the mixture was vacuumed for 15 minutes and the vacuum degree was -0.06 MPa. When the mixture was stirred for 45 hours for the second time, the mixture was vacuumed for 35 minutes and the vacuum degree was -0.03 MPa. After vacuuming, the mixture was stirred in the transverse and axial directions at the same time to obtain a mixed solution III.
[0053] (7) Filling the mixed solution III into a syringe, the filling is carried out by connecting a polymer tube to the filling needle, the outer layer of the polymer tube is polytetrafluoroethylene, the inner layer is silicone rubber, and the hardness of the silicone rubber is 80A.
[0054] Comparative Example 1
[0055] The main difference between Comparative Example 1 and Example 3 is that in step (6), 2 stirrings and 2 vacuumings are changed to 1 stirring and 1 vacuuming, and the other steps are the same as Example 3.
[0056] (6) The homogeneous gel particles are mixed with the mixed solution 1 and vacuumed twice. During the vacuuming process, a condensation baffle is added to the top of the preparation tank and the temperature of the condensation baffle is set to 5°C. Vacuum once and stir for 24 hours. Vacuum for 15 minutes and the vacuum degree is -0.06MPa. After vacuuming, stirring is performed in the horizontal and axial directions at the same time to obtain a mixed solution III.
[0057] Comparative Example 2
[0058] The main difference between Comparative Example 2 and Example 3 is that the main difference between Comparative Example 1 and Example 3 is that in step (6), no condensation baffle is added to the top of the preparation tank, the stirring paddle stirs in one direction, and the other steps are the same as Example 3.
[0059] (6) The homogeneous gel particles were mixed with mixed solution 1 and vacuumed twice. The first time, the mixture was stirred for 24 hours and vacuumed for 15 minutes with a vacuum degree of -0.06 MPa. The second time, the mixture was stirred for 45 hours and vacuumed for 35 minutes with a vacuum degree of -0.03 MPa. After vacuuming, the mixture was stirred horizontally to obtain mixed solution III.
[0060] Comparative Example 3
[0061] The main difference between Comparative Example 3 and Example 3 is that in step (7), the mixed solution 2 is filled into the syringe, and the filling is not connected to the filling needle by a polymer pipeline, but by a commercially available ordinary pipeline. The other steps are the same as those in Example 3.
[0062] (7) Fill the mixed solution III into the syringe using a commercially available common tubing connected to the filling needle.
[0063] Comparative Example 4
[0064] The main difference between Comparative Example 4 and Example 3 is that, (3) after the immersion in step (2) is completed, 25% sodium hydroxide solution is added, the mass volume ratio of sodium hyaluronate, sodium oxide solution and 1,4-butanediol diglycidyl ether in mg / mL is replaced with 10:15:0.2, the stirring time is replaced with 5h, and the other steps are the same as Example 3.
[0065] (3) After the soaking in step (2) is completed, add 25% sodium hydroxide solution, stir for 5 hours, then add 1,4-butanediol diglycidyl ether. The mass volume ratio of sodium hyaluronate, sodium hydroxide solution and 1,4-butanediol diglycidyl ether is 10:15:0.2 in mg / ml to obtain a mixed solution II.
[0066] Positive Control
[0067] Commercially available sodium hyaluronate for injection was used as a positive control, and the manufacturer was Shandong Bausch and Lomb Freda Pharmaceutical Co., Ltd.
[0068] test
[0069] The sodium hyaluronate prepared in Examples 1-3 was tested for pH at room temperature, osmotic pressure at room temperature, elastic modulus at 35° C., viscous modulus at 35° C., and dynamic viscosity at 25° C. The pH value was determined with reference to the glass electrode method (GB6920-86), the osmotic pressure was determined with reference to the 2020 edition of the Chinese Pharmacopoeia, Part III, General Rules 0632 Osmotic Pressure Molar Concentration Determination Method, the elastic modulus and viscous modulus were determined with reference to the international ISO determination standards, and the dynamic viscosity was determined with reference to the ASTM dynamic viscosity measurement standard.
[0070] Table 1
[0071]
[0072] The pH value, osmotic pressure, elastic modulus, viscous modulus and dynamic viscosity tests of the sodium hyaluronate prepared in Examples 1-3 all met the composite standards.
[0073] The sodium hyaluronate prepared by Examples 1-3, Comparative Examples 1-4 and the positive control was subjected to a bubble exclusion test. After analyzing the influence of bubbles in the liquid on ultrasonic measurement, the acoustic attenuation of the liquid with bubbles will increase significantly, and the sound velocity is very unstable. Based on these two characteristics, the single-chip microcomputer technology is used to identify whether bubbles exist in the liquid. The diameter of the ultrasonic converter is 18 mm, the working center frequency is 2.5 MHz, and the time required for each automatic measurement of the sound velocity and sound attenuation is 2 seconds. At an air flow rate of 0.5 L / min, by adjusting the height of the camera, the bubble size and three-dimensional velocity measurement experiments are carried out in different height ranges from the pore outlet. Bubble characteristic measurement experiments are carried out in different height areas. In each group of experiments, the height range of the shooting area is determined by the following method: a scale is placed on the pore, and the image taken by the light field camera is recorded, and the clearest image is determined after refocusing, and the height range of the shooting area is determined according to the range of the scale in the image. The height ranges of the shooting areas of each group of experiments are: 6 cm to 10.5 cm, 8 cm to 12.5 cm, and 10 cm to 14.5 cm.
[0074] Comparative Example 4: After changing the addition amount of sodium hydroxide solution and 1,4-butanediol diglycidyl ether and the stirring time, the elastic modulus at 35°C, the viscous modulus at 35°C and the dynamic viscosity at 25°C were reduced. This shows that in the preparation process of low cross-linking gel, the combination of the ratio of each substance and the production process complement each other, and the product properties obtained by the ratio of the substances and the production process of the present invention are better.
[0075] Table 2
[0076]
[0077] In summary, the present invention provides a method for preparing a sodium hyaluronate composite solution for injection, wherein amino acids, sodium chloride, sodium dihydrogen phosphate, sodium hydrogen phosphate and water for injection are mixed and stirred, and the mixed solution is added to sodium hyaluronate and a low cross-linking gel prepared by polylactic acid microspheres, and the mixture is stirred and vacuumed twice before filling into a syringe. The present invention stirs and vacuums twice, effectively eliminating bubbles, and adds a condensation baffle to the top of the filling, and polymer pipelines are used for transportation and filling, thereby avoiding water loss and quality degradation. The sodium hyaluronate composite solution prepared by the method of the present invention is bubble-free, the pH value of the composite solution is neutral, and the osmotic pressure, elastic modulus, viscous modulus and dynamic viscosity values are relatively good. The preparation method of the sodium hyaluronate composite solution for injection of the present invention, the combination of various steps, is a guarantee for achieving high-quality product quality. In the method, stirring twice, vacuuming twice is changed to stirring once, vacuuming once, or the top of the preparation filling does not add a condensation baffle and a stirring paddle unidirectional stirring, or the filling does not use a polymer pipeline to connect with the filling needle, which will increase the amount of bubbles in the product.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a sodium hyaluronate composite solution for injection, characterized in that: The method comprises the following raw materials in parts by weight: 10-20 parts of sodium hyaluronate, 3-5 parts of polylactic acid microspheres, 0.2-2.0 parts of amino acids, 0.3-1.5 parts of sodium chloride, 0.01-0.06 parts of sodium dihydrogen phosphate, 0.01-0.25 parts of disodium hydrogen phosphate, and 80-90 parts of water for injection, and comprises the following steps: S1. The amino acid, sodium chloride, sodium dihydrogen phosphate, disodium hydrogen phosphate and water for injection were mixed and stirred at room temperature to obtain a mixed solution 1; S2. Weigh sodium hyaluronate and polylactic acid microspheres, and soak them in water for injection for ≥ 6 hours; S3. After the soaking in step S2 is completed, 20-30% sodium hydroxide solution is added, and after stirring for 20-30 minutes, 1,4-butanediol diglycidyl ether is added. The mass volume ratio of sodium hyaluronate, sodium oxide solution and 1,4-butanediol diglycidyl ether is (10-20) mg: (10-12) mL: (0.05-0.15) mL to obtain a mixed solution II; S4. Place the mixed solution II in a water bath at 20-25°C and keep the temperature constant for 10-15h to obtain a low cross-linking gel; S5. The low cross-linked gel was homogenized and granulated, and the sieves for homogenization granulation were 5 meshes, the first mesh was 80 mesh, the second mesh was 100 mesh, the third mesh was 200 mesh, the fourth mesh was 300 mold, and the fifth mesh was 500 mesh to obtain homogenous gel particles; S6. The homogeneous gel particles are mixed with the mixed solution 1, vacuumed twice, and stirred in the transverse and axial directions to obtain a mixed solution III; S7. Fill the syringe with the mixed solution III.
2. The method for preparing a sodium hyaluronate composite solution for injection according to claim 1, characterized in that: The sodium hyaluronate has an intrinsic viscosity of 1.0-3.0 mL / g.
3. The method for preparing a sodium hyaluronate composite solution for injection according to claim 1, characterized in that: The mass ratio of amino acids, sodium chloride, sodium dihydrogen phosphate, disodium hydrogen phosphate and water for injection in S1 is (0.2-2.0):(0.3-1.5):(0.01-0.06):(0.01-0.25):(55-60), and the mass ratio of sodium hyaluronate, polylactic acid microspheres and water for injection in S2 is (10-20):(3-5):(25-30).
4. The method for preparing a sodium hyaluronate composite solution for injection according to claim 1, characterized in that: The stirring in S1 has a rotation speed of 100-200 r / min, a stirring time of 60-100 min, and a temperature of 15-20°C.
5. The method for preparing a sodium hyaluronate composite solution for injection according to claim 1, characterized in that: The particle size of the polylactic acid microspheres is 5-10 microns, and the polylactic acid microspheres are one or more of PLGA, PLGA-PEG, and PLLG-PEG microspheres, and the molecular weight is 10,000-30,000.
6. The method for preparing a sodium hyaluronate composite solution for injection according to claim 1, characterized in that: S6 is vacuumed twice. The first time, when stirring for 20-24 hours, vacuum is drawn for 10-15 minutes, and the vacuum degree is: -0.05~-0.06MPa. The second time, when stirring for 45-48 hours, vacuum is drawn for 30-35 minutes, and the vacuum degree is: -0.02~-0.03MPa.
7. The method for preparing a sodium hyaluronate composite solution for injection according to claim 1, characterized in that: In the vacuuming process of S6, a condensation baffle is added to the top of the preparation tank, the temperature of the condensation baffle is set to 2-5°C, and the stirring paddle stirs horizontally and axially at the same time.
8. The method for preparing a sodium hyaluronate composite solution for injection according to claim 1, characterized in that: S7 describes filling the mixed solution III, which is connected to the filling needle using a polymer pipeline, wherein the outer layer of the polymer pipeline is polytetrafluoroethylene and the inner layer is silicone rubber.
9. The method for preparing a sodium hyaluronate composite solution for injection according to claim 8, characterized in that: The hardness of the silicone rubber is 80-90A.
10. A sodium hyaluronate composite solution for injection, characterized in that Prepared by the preparation method described in claims 1-8.
